Distribution and ecology of Demospongiae from the circalittoral of the islands of the Aegean Sea (Eastern Mediterranean). - Kefalas, E.; Tsirtsis, G.; Castritsi-Catharios, I (Hydrobiologia, 2003)
The distribution and ecology of the sponge fauna of the circalittoral zone of the Aegean archipelagowere studied in the present work. Samples of 64 species of Demospongiae were collected with a sponge-fishing trawl on a network of 23 stations. The hard coralligenous bottoms of the Aegean seem to support the growing of a large number of sponge species with relatively high diversity, whereas rather low abundances were observed for the species collected on soft substrates. Spatial differences were observed in species number and abundance between Northern and Southern Aegean, possibly related to the geomorphological characteristics of the study area. The bathymetric distribution of sponge species in relation to the availability of light in the oligotrophic Aegean is also discussed.